The mediating effect of market orientation on the relationship between total quality management, entrepreneurial orientation and the performance of banks in Libya - Faiz, Goboul Ahmed I. (2015)
The main purpose of this study was to investigate the mediating effect of Market Orientation (MO) on the relationship between total quality management (TQM), entrepreneurial orientation (EO), and organizational performance (OP). The motivation for this study was driven by the inconsistent findings in the literature concerning the relationships between TQM, EO, and organizational performance. Due to the inconsistent results, a new research has emerged and this has prompted further investigation on the effect of other variables that may better explain the nature of these links. In the related literature, many theories have suggested that the compatibility between strategies, resources, and capabilities as the keys for success. To achieve this purpose, this study has integrated different theories such as the resource-based view, and the Congruence Model . Questionnaires were distributed to 400 Sections of the Libyan banks. 230 questionnaires were returned and used in the analysis using the PLSSEM. The results of this study revealed that TQM, and EO were positive and have also been proven to be significant predictors of organizational performance. More importantly, the results have also confirmed the mediating effect of Market Orientation on the relationships between TQM, EO, and organizational performance